Pengaruh Moral Reasoning, Retaliasi, Ethical Sensitivity dan Komitmen Profesional terhadap Niat Melakukan Whistleblowing - Deby Nofrizaldi; Nayang Helmayunita (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to analyze the effect of moral reasoning, retaliation, ethical sensitivity, and professional commitment on the intention to whistleblowing. This research is an associative causality study with a quantitative approach. The population in this study were all employees of the Padang Pariaman Regency DPUPR, Padang Pariaman Regency DPMPTP, and Padang Pariaman Regency BPKD. The data collection method used a questionnaire that was distributed directly. The data used in this study is primary data. The hypothesis in this study was tested using multiple linear regression analysis. The results show that moral reasoning has a positive effect on the intention to do whistleblowing, retaliation has a negative effect on the intention to do whistleblowing, ethical sensitivity has no effect on the intention to do whistleblowing and professional commitment has a positive effect on the intention to do whistleblowing.